Modern issues of pedagogy and psychology: theoretical and methodological approaches and practical research results - Gadzaova L. P., Makambaeva Y. Z., Murzaeva B. T., Satyvaldiev A. S., Shemiakina S. A., Sakharchuk E. I., Anikin V. M., Kupovykh G. V., Ryspaeva C. K., Akhunzhanova M. K., Maslennikova S. F., Medvedeva A. A., Temirkanova T. E., Doroschuk E. S., Zaritskaia V. V., Kozlova M. A., Kozlov A. V., Sabodina E. P., Kugai A. I., Kugai A. I., Bashkireva T. V., Bashkireva A. V., Shatokhina L. V., Smykovskaia T. K., Sergeev N. K., Korotkov A. M., Korepanova M. V., Rodionova I. V., Shapirova R. R., Akhtarieva R. F., Khotuliova O. V., Egorova G. V., Barashkina S. B., Zaluzhnaia M. V., Kostenko E. G., Kugai A. I., Isakova T. I., Zanin D. S. (Modern issues of pedagogy and psychology: theoretical and methodological approaches and practical research results, 2025)
one of the key challenges associated with the introduction of digital technologies is changing the structure and form of reading. Schoolchildren increasingly prefer short, visually rich texts, which affects their ability to perceive more complex, multi-layered literary works. To improve the level of reading literacy, it is necessary to develop comprehensive approaches that take into account the opportunities and limitations of the digital environment so that every student can maximize the benefits of using modern technologies in education. The authors considered the psychological and pedagogical aspects of the impact of digitalization on the development of reading literacy in schoolchildren, analyzed the experience of using digitalization to develop reading literacy in schoolchildren, and identified the levels of reading literacy. To solve the tasks set, scientific tools were used, including comparative and statistical analysis, study and analysis of research carried out in the field of school education, study of regulatory documents, modeling, observation, study of educational products, and questionnaires.
Keywords: образование; education; цифровизация; digitalization; читательская грамотность; reading literacy